RECYCLING OF MUNICIPAL SOLID WASTE FOR ELECTRCITY GENERATION AND GREEN EARTH - Sathish Raj , C.Deepthi, A. Benuel (International Journal of Scientific Research and Management (IJSRM), 2014)
Waste generation is increasing everywhere. Hence improved waste management is an essential element to make the resource efficient. Municipal Solid Waste (MSW), generated if not properly managed, causes health and environmental issues. The conventional method of solid waste management is land filling and incineration. Though, these methods have proven advantages, they have drawbacks such as place occupation, smell and Green House Gases (GHG). This paper focuses on the recycling of MSW in a Bubbling Fluidized bed reactor. Furthermore, the modeling of a Far-infrared heater to heat the Bubbling Fluidized Bed Reactor is also carried out. Moreover, the composition of synthesis gas with reduced tar and char composites is also obtained and the optimum parameters for efficient energy production are identified from the available municipal solid waste.